Apatite Trace Element Compositions: A Robust New Tool for Mineral Exploration - Mao, Mao; Rukhlov, Alexei S.; Rowins, Stephen M.; Spence, Jody; Coogan, Laurence A. (Economic Geology, 2016)
Apatites from the major types of mainly magmatic-hydrothermal mineral deposits (30 localities, mostly in British Columbia, Canada) together with apatites from carbonatites (29 intrusive complexes) and unmineralized rocks (11 localities) have been analyzed by electron microprobe and laser ablation-inductively coupled plasma mass spectrometry. Discriminant analysis using Mg, V, Mn, Sr, Y, La, Ce, Eu, Dy, Yb, Pb, Th, and U reveals that apatites from mineral deposits can be distinguished from apatites in carbonatites and unmineralized rocks. Apatites from mineral deposits are characterized by higher Ca and correspondingly lower total contents of trace elements that partition onto the Ca sites (rare earth elements (REEs), Y, Mn, Sr, Pb, Th, and U) than apatites from unmineralized rocks and carbonatites. Apatites from the different deposit types also have distinct trace element compositions that are readily discriminated by the discriminant functions. Apatites from worldwide carbonatites have the most fractionated REE distributions with light REE enrichment (Ce/YbCN = 35–872), high V (1.6–1,466 ppm), Sr (1,840–22,498 ppm), Ba (1.8–275 ppm), and Nb (0.4–19 ppm) contents, the lowest W contents (0.05–0.55 ppm), and no significant Eu anomalies (Eu/Eu* = 0.9–1.2). Apatites from alkalic porphyry Cu-Au deposits in the North American Cordillera possess high V contents (2.5–337 ppm), whereas apatites from calc-alkaline porphyry Cu-Au and Cu-Mo deposits have high Mn contents (334–10,934 ppm) and typically large negative Eu anomalies (Eu/Eu* = 0.2–1.1). Apatites from iron oxide Cu-Au (IOCG) and related Kiruna-type iron oxide-apatite (IOA) deposits in Canada, China, and Mexico typically have large negative Eu anomalies (Eu/Eu* = 0.2–1.5) and low Mn contents (40–5,753 ppm). Apatites from orogenic Ni-Cu, porphyryrelated Cu-Au breccia, Au-Co skarn, Pb-Zn skarn, and Cu skarn deposits have relatively low abundances of impurity cations. This study demonstrates that detrital apatite grains collected during regional geochemical surveys ...